2009
DOI: 10.1089/lap.2008.0408
|View full text |Cite
|
Sign up to set email alerts
|

Management of Recurrent Inguinal Hernias After Total Extraperitoneal (TEP) Herniorrhaphies

Abstract: Laparoscopic repair can be offered to those patients with a recurrence after a previous laparoscopic repair. Further studies comparing laparoscopic repair versus open repair of recurrences after laparoscopic inguinal hernia repair will be helpful in defining the best approach when encountering these recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…However, it must be stated that the reported follow-up in the included studies that reported recurrence in the current pooled analysis was as short as 1 year in some studies, and that more long-term results would add weight to the findings [17][18][19][20]. Previous studies of causes for recurrence following laparoscopic inguinal hernia repair have identified operative inexperience, inadequate dissection, folding or twisting of the prosthesis, and insufficient hernia defect overlap as risk factors [27,28]. Given the current evidence, mesh weight cannot be added to this list.…”
Section: Study or Subgroupmentioning
confidence: 85%
“…However, it must be stated that the reported follow-up in the included studies that reported recurrence in the current pooled analysis was as short as 1 year in some studies, and that more long-term results would add weight to the findings [17][18][19][20]. Previous studies of causes for recurrence following laparoscopic inguinal hernia repair have identified operative inexperience, inadequate dissection, folding or twisting of the prosthesis, and insufficient hernia defect overlap as risk factors [27,28]. Given the current evidence, mesh weight cannot be added to this list.…”
Section: Study or Subgroupmentioning
confidence: 85%
“…The strength of this study is the length of follow‐up and a robust follow‐up, which comprised outpatient clinical examinations, a review of national electronic medical records, and standardized phone consults with each patient to evaluate the long‐term outcomes. With median follow‐ups of 43 and 45 months, we believe this study adequately addressed concerns regarding late recurrences . In addition, all the surgeries were performed using the same mesh type and size.…”
Section: Discussionmentioning
confidence: 98%
“…This would then expose the normal mesh to bowel-causing adhesions with possible deleterious sequelae. Indeed, Lo Menzo et al 8 showed, in a series of 6 patients with 7 recurrent inguinal hernias after laparoscopic repairs, there were 2 cases where the peritoneal flap was not able to cover the mesh and a tissue-separating mesh with fibrin sealant had to be used to cover the myopectineal orifice. Additionally, the TAPP repair involves placement of a 10-mm trocar through the linea alba in the umbilical region and 2 × 5 mm trocars more inferiorly (although some surgeons prefer to place these latter trocars laterally on each side of the abdomen), all of these trocar sites are at risk of port-site hernia formation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there are experts in laparoscopic inguinal hernia repair who have successfully attempted relaparoscopic repair, but this practice is confined to very few surgeons in specialized hernia centers. 7,8 On the other hand, surgeons who are confident with laparoscopic ventral hernia repair and total extraperitoneal (TEP) or transabdominal preperitoneal (TAPP) repair might consider the intraperitoneal onlay mesh (IPOM) repair as merely an extension of laparoscopic ventral hernia repair, although detailed knowledge of the laparoscopic extraperitoneal inguinal anatomy would be essential. 9 …”
Section: Introductionmentioning
confidence: 99%